Pemetaan Aksara-Silabel Berbasis Grafem Aksara Bali dalam Kamus Bali – Indonesia Beraksara Latin dan Bali Tahun 2016 - Paramarta, I Ketut; Martha, I Nengah; Astiti, SG. Laksmi Widi Candra (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
The representation of syllables, which are realized through akshara, often gives rise to ambiguity in their phonological mapping, consequently impacting reading and writing performance.The objective of this study is to describe how syllables are represented by Balinese script graphemes within Balinese-Indonesian dictionaries with Latin and Balinese scripts in 2016. The list of Balinese script entries that make up the Balinese – Indonesian Latin and Balinese Dictionary totals 16,162. The graphemic analysis of each basic shape of the Balinese script (specifically the Wreastra type) employed in the entries is conducted based on linguistic value criteria from Meletis (2019). The validated Balinese script represents language units at the hidden syllable level, allowing for the analysis of phonological syllable structure information based on the Balinese syllable pattern. The research findings indicate that the Balinese script graphemes represent syllables using CV and V patterns. The Balinese script grapheme that represents CV (/Ca/ and /Cә/) is realized by the main consonant grapheme group and its paired variant. Syllables with a V pattern, on the other hand, are formed through a combination of free graphemes representing glottal stop consonants (/ha/) and bound graphemes in the form of diacritics used for vowel markers other than attached vowels, that is ulu /i/, pepet /ǝ/, taleng /e/, taleng tedong /o/, and suku /u/.